My Ipad Mini - Rosenzweig, Gary (Que, 2012)
Covers iOS 6 Step-by-step instructions with callouts to iPad mini photos that show you exactly what to do. Help when you run into iPad mini problems or limitations. Tips and Notes to help you get the most from your iPad mini. Full-color, step-by-step tasks walk you through getting and keeping your iPad mini working just the way you want. Learn how to: Connect your iPad mini to your Wi-Fi and 3G/4G LTE networks; Record and edit video using iMovie for iPad mini; Use Siri to control your iPad mini or get information by speaking commands; Take photos, and then edit them using iPhoto for iPad mini; Video chat with your friends using Skype and FaceTime; Stream audio and video to Apple TV and other devices; Use Dictation to create notes, emails, text messages, search the Internet, and more; Use iCloud to synchronize data between your devices; Watch movies, TV shows, or home videos; Surf the Web, and send and receive email; Download apps to make your iPad mini even more useful; Manage your contacts, and then connect with others using Messaging; Stay organized with the Calendar app; Use Pages and Numbers to create documents and spreadsheets; Use Keynote to build and display presentations.